The Effect of Social Factors, Prices, and Product Features on Purchase Intention of Yamaha NMAX Motorcycles at State Polytechnic of Bengkalis Students - Alfi Suhaila; Nageeta Tara Rosa (Jurnal Pemimpin Bisnis Inovatif, 2024)
The development of the business world in the current era of globalization is increasingly sharpening competition, especially in the management of automotive company units. One type of automotive that is widely favored by Indonesians is motorcycles. This study aims to determine the Effect Social Factors, Prices, and Product Features on Purchase Intention of Yamaha NMAX Motorcycles at State Polytechnic of Bengkalis Students. This study uses quantitative methods, data collection techniques are carried out by distributing online questionnaires with a sample of 100 respondents. The sampling technique used non- probability sampling method, data analysis used is descriptive statistics, classical assumption test, multiple regression analysis, data conclusion with T test, F test and the coefficient of determination (R2), while data processing used SPSS version 26 program. The findings indicate that social factors and product features variables have an effect, meanwhile the prices variable does not have an effect on purchase intention of Yamaha NMAX motorcycles at State Polytechnic of Bengkalis students. This study provides the insight that Yamaha can direct efforts and resources towards social marketing and product feature enhancement rather than focusing on price adjustment strategies.